THE CONSTITUTIONAL PARADOX OF THE REGIONAL REPRESENTATIVE COUNCIL: RECONSTRUCTION OF DPD AUTHORITY IN AN ASYMMETRICAL BICAMERAL SYSTEM IN INDONESIA - Muhammad Syaripudin Amin; Rineke Sara (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2026)
Constitutional reforms following the Reformation era established the Regional Representative Council as a body embodying territorial interests, intended to amplify provincial voices within national lawmaking. Yet, its practical powers remain constrained, yielding a contradiction between robust democratic endorsement via popular elections and circumscribed legislative influence. This inquiry dissects the configuration of the Regional Representative Council's authority within Indonesia's constitutional architecture and proposes a paradigm for reconfiguring its role amid an asymmetrical bicameral framework. Adopting normative juridical methodology with statute-oriented, conceptual, and comparative lenses, data derive from archival examinations of legislation, Constitutional Court rulings, and pertinent constitutional scholarship. Findings reveal Indonesia's bicameral structure as predominantly soft bicameralism, wherein the House of Representatives predominates legislatively, relegating the Regional Representative Council to consultative rather than determinative participation. The analysis introduces the asymmetric bicameral constitutional paradox notion alongside a balanced asymmetrical bicameralism paradigm to realign the Council's powers, enhancing territorial advocacy while preserving unitary state principles. These insights enrich theoretical discourse on bicameralism in unitary systems and furnish a foundational blueprint for parliamentary restructuring in Indonesia.